Studies on the toxicological effect of nevirapine, an antiretroviral drug, on the liver, kidney and testis of male Wistar rats (2011)
African Journal of Biotechnology Vol. 8 (6), pp. 941-948,We investigated the toxic effect of nevirapine (NVP; Viramune1), an antiretroviral drug, on the liver, kidney and testis of Wistar rats. Twenty-one rats were assigned into 3 groups of 7 animals each. The first group served as control, and the second and third groups received NVP at 18 and 36 mg/kg body weight, respectively. Clinical signs of toxicity were not observed in the animals. NVP at both doses did not significantly (p > 0.05) alter the body weight gain, relative weights of kidney and testis, serum protein, urea, creatinine and alkaline phosphatase levels of the animals. However, NVP2 significantly (p < 0.05) increased the relative weight of liver, level of serum total bilirubin and activities of g-glutamyl transferase, alanine and aspartate aminotransferases. NVP administration caused a dose-dependent, significant (p < 0.05) elevation of lipid peroxidation measured as malondialdehyde (MDA) content in the liver, kidney and testis of the rats. Hepatic, renal and testicular MDA were increased by 107%, 80% and 163%, respectively, in NVP2-treated rats. Elevation in MDA was accompanied by a significant (p < 0.05) decrease in the activities of hepatic, renal and testicular superoxide dismutase and catalase. NVP2 caused 43% and 32% decrease in spermatozoa motility and live/dead sperm count, respectively, and 94% increase in total sperm abnormalities. Histopathological findings showed that NVP2 caused degeneration of seminiferous tubules in testis, and severe necrosis in liver slides. NVP induced oxidative stress with corresponding decrease in antioxidant status of the rats. The changes in sperm parameters and, elevation of liver marker enzymes suggest an interference of NVP2 with these organs.